Unveiling photoluminescent response of Ce-doped CaCu3Ti4O12: An experimental-theoretical approach - Moreno, H. [UNESP] (2022)
CaCu3Ti4O12: x% Ce (x = 0.00, 0.25, 0.50, 0.75, and 1.00) ceramic composites were prepared via solid-state reaction. Theoretical atomistic simulations were combined with experimental techniques to uncover Ce effects in the (micro)structure and photoluminescence of CaCu3Ti4O12-based ceramics. Application of perovskites ceramics in optoelectronics have been limited by their specific, narrow emission range, which compromise operational efficiency, pushing for the development of novel perovskite-emissive materials. This study results confirm that Ce ions are incorporated at Ca sites within the CaCu3Ti4O12 lattice, inducing point metal and oxygen vacancies in the optical bandgap region. Shallow-level defects (VCa′′/VO⦁⦁) were associated with broadband violet-blue photoluminescent (PL) emissions. Better color rendering may be a direct consequence of crystalline field splitting/wider PL emission. Furthermore, results demonstrate that PL on CaCu3Ti4O12: Ce system intensity can be modulated by structural defects, making it promising for applications in optoelectronics.